Dynamic cache size transfer scheme based on replacement rate in content centric networking - EGuo-dong G; UOYun-fei G; ANJu-long L; IUCai-xia L (Tongxin xuebao)
How to allocate an appropriate cache size to each router and efficiently utilize the finite storage resources poses challenges to the caching performance in CCN (content centric networking).On the basis of homogeneous cache allocation,a dynamic cache size transfer scheme based on replacement rate is proposed.In the scheme,the rationality of the cache size transfer is demonstrated firstly.And then,according to the level of actual demand for the storage resources,the cache transfer procedure is implemented dynamically on the nodes which have different caching states.The idle cache resources are temporarily transferred to the overload node to reduce cache miss rate and enhance the caching gain.The simulation results show that,with a small amount of additional cost,the proposed scheme can efficiently decrease the re-quest hops,increase the cache hit ratio,and improve the overall utilization of storage resources.